Molecular cloning of the human cholecystokinin gene by use of a synthetic probe containing deoxyinosine. - Takahashi, Y (1985)
A synthetic DNA based on the known amino acid sequence of the brain/gut peptide cholecystokinin (CCK) was synthesized. This DNA contained deoxyinosines at ambiguous codon positions and was used as a probe to isolate the CCK gene directly from a human genomic library. Nucleotide sequence analysis of the isolated gene revealed that human preprocholecystokinin consists of 115 amino acid residues, with 11 amino acids in common with the human gastrin precursor, another member of the gastrin-CCK family, and that the coding region is separated by a single, long intron. CCK appears to be encoded by a single-copy gene in the haploid human genome, as revealed by genomic Southern hybridization analysis, suggesting that the same gene is expressed both in gut and brain.